The power of words : unveiling the speaker and writer's hidden craft - Kaufer, David S. (Lawrence Erlbaum, 2004)
Over the past several years, David Kaufer and his colleagues have developed a software program for analyzing writing (DocuScope). This book illustrates the concepts and rhetorical theory behind the software analysis, examining patterns in writing and showing writers how their writing works in different categories to accomplish varying objectives.